Evaluation of the Pharmacotherapeutic Pattern for Treating Schizophrenia in Bangladesh - Salsabil Islam; Md. Sohan; Faysal Ahmed; Zabun Nahar; Md. Rabiul Islam (Mazandaran University of Medical Sciences, 2020)
Background: Studies of the pharmacotherapeutic pattern on schizophrenic patients are few clinical therapy is one of the bases for the assessment of the treatment of Schizophrenia. Objectives: This study aimed to analyze the demographics of these patients along with current trends of drug prescribing practice in Bangladesh. Methods: This survey was conducted over 6 months at the National Institute of Mental Health, Dhaka, Bangladesh, and Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh. A total of 250 subjects were investigated and their prescriptions were verified to obtain necessary information regarding pharmacotherapy. Non-cooperation and negative consent lead to exclusion from the study sample. Results: Out of 250 patients, the frequency of female patients was higher (54.4%) than that of the male patients (45.6%). Therefore, the gender ratio was female-biased. We found that 63.6% of the patients suffering from schizophrenia were above 25 years old. The treatment approach of schizophrenia includes pharmacotherapy and or psychotherapy. In this study, we found that the highest medication used in the treatment was antipsychotic drugs (n=388, 46.58%) followed by anticholinergic drugs (n=217, 26.05%) and anxiolytic drugs (n=172, 20.65%). Conclusion: The overall prescribing method for schizophrenia in Bangladesh complies with the authorized practiced guidelines and treatment pattern of the developed countries as well as authorized guidelines.